Land economics and policy in developing countries - Mohanty, P. K. (Prasanna Kumar) 1954- (SAGE Publications India Pvt Ltd, 2022)
"Land economics is grossly neglected in developing countries, including India. The disconnect between land use planning through master plans and land economics is glaring. Master planning has led to an acute scarcity of serviced land and floor space for economic growth and affordable housing. It has resulted in sprawl, housing-employment mismatch, environmental degradation, social exclusion, rent-seeking and deadweight welfare losses. Land Economics and Policy in Developing Countries delves into theory and practice of land economics to draw lessons for land policy and management. It presents concepts and perspectives of land, functioning of land markets, determinants of location and land use, fallacies of comprehensive land use planning, sustainable land management design, land-based financing of infrastructure and land policy reforms in developing countries"--